Phenolics content and antioxidant activity of wood extractives from three clones of acacia hybrid (Acacia mangium × Acacia auriculiformis) - Aristo Verick Purba, Brandon; Sunarti, Sri; Lukmandaru, Ganis (Maderas. Ciencia y Tecnología, 2021)
The objective of this study was to investigate the extractive content of three fast growing Acacia hybrid clones (Clone 16, 25, and 44) wood in three radial directions (SW = sapwood; OHW = outer heartwood; IHW = inner heartwood); total phenolic, flavonoid, flavanol contents (colorimetric assay); and antioxidant activity (1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging assay). Extractions were done with three different solvents in successive (n-hexane = H; methanol = M; hot water = W), yielded 0,69 % – 1,70 %; 1,51 % – 10,86 %; and 0,51 % – 1,16 % of extractive contents, respectively. The total phenolic content (TPC) from TPC-H, TPC-M, and TPC-W ranged between 3,68 mg of gallic acid equivalent (GAE)/g – 10,41 mg GAE/g; 76,83 mg GAE/g – 448,35 mg GAE/g; and 43,28 mg GAE/g – 198,92 mg GAE/g, respectively; the total flavonoid content (TFC) from TFC-H, TFC-M, and TFC-W between 4,23 mg of quercetin equivalent (QE)/g – 41,51 mg QE/g; 29,55 mg QE/g – 133,71 mg QE/g; and 7,70 mg QE/g – 29,37 mg QE/g, respectively; total flavanol content (TVC) from TVC-H, TVC-M, and TVC-W ranged between 28,74 mg of catechin equivalent (CE)/g – 66,90 mg CE/g; 83,39 mg CE/g – 247,18 mg CE/g; and 7,08 mg CE/g – 29,21 mg CE/g, respectively. Furthermore, the antioxidant activity was found to be significantly affected by the radial factor with the strongest activity exhibited by inner heartwood extract with an IC50 value of 255,77 μg/ml (gallic acid IC50 showed a value of 39,00 μg/ml). Among clones, clone 16 was determined to have the highest extractive, total flavonoid as well as flavanol contents. Thus, clone 16 was hypothesized to be more resistance against heart rot disease.